Pengembangan Media Video Scribe pada Materi Rantai Makanan Kelas V SDN Mojorot 4 Kota Kediri - Yuda Agung Prasetyo; Kukuh Andri Aka; Nurita Primasatya (Departement of Mathematics Education, 2022)
This research is motivated by the results of observations made in class V SDN MOJOROT 4 Kediri City, and the absence of learning media that can increase students' learning motivation, because in the learning process teachers tend to teach learning only theoretically and concepts. Abstract concepts. So that students get bored easily and find it difficult to understand the material presented by the teacher during the learning process. With the existence of this video scribe learning media, it is hoped that the teacher will be able to increase the learning motivation of elementary school students. The purpose of this study was to determine the validity, practicality and effectiveness of using video scribe media on food chain materials for class V students. This research is a development study using the ADDIE model. The ADDIE model consists of 5 stages, namely the stages of Analysis, Design, Development, Implementation, Evaluation. The data collection instruments used were material expert validation sheets, medical experts, teacher practicality questionnaires, student effectiveness questionnaires and written tests / evaluation questions. Data from the validation of questionnaires and written tests/evaluation questions used a Likert scale. The results of the research on the development of video scribe media are (1) the video scribe media is said to be valid by obtaining a percentage of 90% material experts. While the results of media experts are 81%. (2) the video scribe media is said to be practical by obtaining results from teacher questionnaires of 92.5% and student response questionnaires of 93%. (3) the video scribe media is said to be effective after a limited trial by giving post-test questions to get 80% results so that the video scribe media can be said to be effective to use